WHAT IS 'REPUBLICANISM'? REPUBLIC AS 'A FORM OF AUTHORITIES' AND AS 'A FORM OF RULE' - Savanović, Aleksandar (Politeia, 2023)
In this paper, we discuss  the meaning of the words 'republic' and 'republicanism'. These words are classic political terms, frequently used in political theory and political practice as well. Still, do they convey clear and unambiguous meaning to everybody? Is it possible to find a single sense and meaning of the word republic/republicanism? Is something like that even necessary? How to understand and justify the intense contemporary scientific discussion on that topic? In general, it is possible to use three types of classification. First, we can analyze different theories of republicanism, such as the ones we have in the works of Machiavelli, Kant, and alike. Secondly, it is possible to analyze the different historical forms of the notion of republic - for example, Roman Republic, Republic of Venice, or the United States. Thirdly, we can analyze  different doctrines of republicanism, such as the so-called liberal republicanism or civic republicanism. In this text we will go through these forms of republic and republicanism using the Kantian formula of 'government' and 'sovereignty'.
Keywords: Republicanism; rule; authorities; republic